On Some New Sequence Spaces and Their Duals - Damla Barlak (Journal of Mathematics)
In this study, we defined some new sequence spaces using regular Tribonacci matrix. We examined some properties of these spaces such as completeness, Schauder basis. We have identified α−,β−, and γ−duals of the newly created spaces.